MEASUREMENTS of the SUNYAEV-ZEL'DOVICH EFFECT in MACS J0647.7+7015 and MACS J1206.2-0847 at HIGH ANGULAR RESOLUTION with MUSTANG - Young, A.; Mroczkowski, T.; Romero, C.; Sayers, J.; Balestra, I.; Clarke, T.; Czakon, N.; Devlin, M.; Dicker, S.; Ferrari, C.; Girardi, M.; Golwala, S.; et al. (Institute of Physics Publishing, 2015)
We present high resolution (9?) imaging of the Sunyaev-Zel'dovich Effect (SZE) toward two massive galaxy clusters, MACS J0647.7+7015 (z = 0.591) and MACS J1206.2-0847 (z = 0.439). We compare these 90 GHz measurements, taken with the Multiplexed Squid/TES Array at Ninety Gigahertz (MUSTANG ) receiver on the Green Bank Telescope, with generalized Navarro-Frenk-White (gNFW) models derived from Bolocam 140 GHz SZE data as well as maps of the thermal gas derived from Chandra X-ray observations. We adopt a serial-fitting approach, in which gNFW models are first fit to the Bolocam data and then compared to the MUSTANG data to determine an overall best-fit model. For MACS J0647.7+7015, we find a gNFW profile with core slope parameter ? = 0.9 fits the MUSTANG image with and probability to exceed (PTE) = 0.34. For MACS J1206.2-0847, we find , , and PTE = 0.70. In addition, we find a significant (>3s) residual SZE feature in MACS J1206.2-0847 coincident with a group of galaxies identified in Very Large Telescope data and filamentary structure found in a weak-lensing mass reconstruction. We suggest the detected sub-structure may be the SZE decrement from a low mass foreground group or an infalling group. Giant Metrewave Radio Telescope measurements at 610 MHz reveal diffuse extended radio emission to the west, which we posit is either an active galactic nucleus-driven radio lobe, a bubble expanding away from disturbed gas associated with the SZE signal, or a bubble detached and perhaps re-accelerated by sloshing within the cluster. Using the spectroscopic redshifts available, we find evidence for a foreground (z = 0.423) or infalling group, coincident with the residual SZE feature.